ADB's Role towards Energy Infrastructure Development: Case of Post-COVID-19 Pandemic in Indonesia - Ferdian Ahya Al Putra (Institute of International Studies, 2021)
ADB is a strategic partner for Indonesia in Development. Public sector management and energy are two sectors that the both parties focus on. On the last few years, Indonesia focusses on the climate change, therefore energy infrastructure is being pursued by Indonesia in order to develop the renewable energy. Unfortunately, in the midst of pursuing this goal, Indonesia is facing the COVID-19 Pandemic that affect various sectors in Indonesia. The pandemic gave impacts on infrastructure development in Indonesia, including energy infrastructure. This research examines the ADB's Approach towards Energy Infrastructure Development in Indonesia, specified on case of post-COVID-19 Pandemic. This research applied descriptive qualitative method and used international organization theory for analysis. Moreover, this research used the literature study technique to obtain the relevant data. The result shows Indonesia and ADB have cooperation on handling COVID-19 Pandemic. But, cooperation on infrastructure development still being the priority of both parties. Both parties seek for solution for economic recovery without sacrificing project on infrastructure development, especially on energy sector.